CREATIVE IMAGINATION, TRAGIC-POETIC ART AND EDUCATION OF SENSIBILITIES - Silva, Luzia Batista de Oliveira; Tavernard, Ivone Oliveira; Tavernard, Junior (Revista Inter-Legere, 2018)
Luzia Batista de Oliveira Silva, Ivone Oliveira Tavernard, Junior Tavernard This article aims to discuss about how creative imagination, tragic art and the education of sensibilities provides images of dreams of flying, ascension and freedom, contributing to the understanding of a poetic education of the child and the adult. The aesthetics of the poems and the literary lessons attest that art educates the sensibilities. We recognize this in Bachelard when he approaches the education-poetics in childhood and in the tragic-poetic art of Nietzsche, according to The Birth of Tragedy and Thus Spoke Zarathustra. In these works, the images are full of dreams of freedom represented in the ascents to the mountain summit, in the pure air breath and in the contemplation of aerial landscapes, which enables the individual -from a privileged position - to become a lover of life, who refuses its heavy side, its dark elements, the melancholy atmosphere, the disseminated Greek serenity. The heights, the silence against the crowd and the noise, as well as "states of soul" - in Bachelard's vision and analysis of the work "Thus spoke Zarathustra" - are at the same time exalted and reveals the dreams of freedom, of ascension and moral elevation. Keywords: Culture. Poetic Education. Aesthetics. Bachelard. Nietzsche.